Simulation analysis of the influence of internal surface morphology of mini‐channel on battery thermal management. (11th June 2020) - Yang, Yi; Xu, Xiaoming; Li, Wenchao; Tong, Guangyao
Summary: Lithium‐ion batteries, as the only source of driving force for electric vehicles (EV), directly determine the vehicle's power performance, driving mileage, and working stability. The performance, safety, and longevity of lithium‐ion batteries are related to battery temperature. In this article, surface topography has been added in mini‐channel liquid cooling plate, the influence of different shapes, different heights, different diameters, and different numbers of surface topography on the cooling effect of mini‐channel liquid cooling plate were researched by using CFD method. This article revealed that the addition of surface topography in mini‐channel can affect the flow trajectory of coolant and improve the cooling capacity of the cold plate. When five cylindrical surface topography with a diameter of 10 mm and a height of 1.5 mm were added in each channel, the highest temperature of the battery can be suppressed to 42.01°C and the maximum temperature difference can reach 15.78°C under 3C discharge rate, compared with the smooth mini‐channel, decreased by 1.02°C and 0.85°C, respectively. Abstract : In this article, surface topography has been added in mini‐channel liquid cooling plate, the influence of different shapes, different heights, different diameters, and different numbers of surface topography on the cooling effect of mini‐channel liquid cooling plate were researched by using computational fluid dynamics method. This article revealed that the addition of surface topography in mini‐channel can affect the flow trajectory of coolant and improve the cooling capacity of the cold plate.